FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENINGKATAN BERAT BADAN PENGGUNAA ALAT KONTRASEPSI DMPA - Woro Tamia Nuningtias (LPPM Widyagama Husada Malang, 2025)
Background : In Indonesia, DMPA has the largest percentage, namely 49.9% for new acceptors and 47.78% for old acceptors (Ministry of Health, 2022). In West Java, the highest users of DMPA injection contraception are in Bekasi Regency with 104,297 acceptors (BPS Jabar. 2020). Based on data from the West Java Health Office in (2021), the central statistics agency explained that the number of Fertile Age Couples (PUS) was 9,333,302 participants. With details of 562,771 (54.7%) users of injectable contraception. One of the side effects that often occurs in the use of DMPA injectable contraception is weight gain. This effect is caused by the hormone progesterone which facilitates the transformation of carbohydrates and sugars into fat, so that fat reserves under the skin increase. The purpose of the study was to determine the relationship between maternal age, duration of use, physical activity, history of diabetes, and diet with weight gain in DMPA contraceptive users at TPMB Salifiyah in 2024. Subjects and Methods : This type of research uses observational analytics with a cross-sectional approach with a population of 60 respondents, in sampling using a total sampling of 60 samples, the results of which are processed by editing, coding, processing, scoring and tabulating which will be analyzed using univariate analysis and bivariate analysis. Result : It was found that all the variables studied had a significant relationship, maternal age >35 years (p=0.000) there was a relationship and there was a 44 times greater risk of increasing body weight, duration of use >2 years (p=0.000) there was relationship and a 4.8 times greater risk of this occurring increased body weight, heavy physical activity (p=0.018) there is a relationship and light physical activity has a 6.5 times higher risk of increasing body weight compared to moderate and heavy activities, a history of diabrt (p=0.000) with a relationship and a history of diabetes has a 14.5 times higher risk of occurring there is a relationship between, increasing body weight and having a good diet (p=0.000) and there is a 7.5 times greater risk of increasing body weight compared to a moderate diet and 7.5 times comparedto a poor diet. Keywords: Weight gain, DMPA, age, duration of injection use, physical activity, history of diabetes, diet.